1.0 s Ultrafast MRI in non-sedated infants after reduction with spica casting for developmental dysplasia of the hip: A feasibility study. (June 2016) - Fukuda, Atsushi; Fukiage, Kenichi; Futami, Tohru; Miyati, Tosiaki
Purpose: The aim of this study was to first develop and use 1.0 s ultrafast magnetic resonance imaging (MRI) to confirm the location of the femoral head in non-sedated infants with developmental dysplasia of the hip (DDH) after reduction with spica cast application in clinical settings. Methods: The ultrafast acquisition was achieved by employing a balanced steady-state free precession sequence and immobilizing the patient with dedicated sandbags. On completion of the ultrafast MRI study, all infants were sedated for conventional MRI scanning. Two orthopaedic surgeons retrospectively evaluated the image quality, result of the reduction and total MRI study time (including patient immobilization, coil setup, and scanning) in 14 DDHs of 13 infants (one with bilateral DDHs). Results: Both reviewers stated that there were no motion artefacts for non-sedated infants during the ultrafast MRI and that the quality of both the ultrafast and conventional MRI images were acceptable to assess the femoral head location. Assessment of the reduction procedure resulted in two hips being categorized as 'incomplete reduction' requiring a re-reduction procedure. The total study time of ultrafast and conventional MRI was 6 ± 1 min and 14 ± 3 min, respectively ( P < 0.001). No complications due to sedation, such as hypoxia, were reported. The average sedation waiting time was 1 h 25 min ± 34 min. Conclusion: The ultrafast MRI procedure reported here can be readily employed to confirm the location of the femoral head in infants with DDHs, without the use of any sedation.